2011
DOI: 10.1099/ijs.0.026799-0
|View full text |Cite
|
Sign up to set email alerts
|

Halolamina pelagica gen. nov., sp. nov., a new member of the family Halobacteriaceae

Abstract: Halolamina pelagica gen. nov., sp. nov., a new member of the family Halobacteriaceae Two extremely halophilic archaeal strains, TBN21 T and TBN49, were isolated from the Taibei marine solar saltern near Lianyungang city, Jiangsu province, China. Cells of the two strains were pleomorphic and Gram-negative and colonies were red. Strains TBN21 T and TBN49 were able to grow at 25-50 6C (optimum 37 6C), at 1.4-5.1 M NaCl (optimum 3.4-3.9 M) and at pH 5.5-9.5 (optimum pH 7.0-7.5) and neither strain required Mg 2+ fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 34 publications
1
42
0
Order By: Relevance
“…Prior studies have identified members of the Halorubrum and Haloquadratum and, in some samples, Halonotius, Natrinema, and Haloferax as dominant members of crystallizer salterns (8,45,47), while in our study, members of the recently described genera Halogranum, Halolamina, Halosarcina Halorientalis, and Haloplanus represented a major fraction of the Halobacteriales community in multiple habitats (e.g., 60.8, 66.4, 41.1, and 49.4% in MAN, ZDT, CAR, and SPL, respectively). This attests to the relevance and significance of recent efforts for the isolation and characterization of novel Halobacteriales genera in various habitats beyond typical hypersaline water bodies (14)(15)(16)(17)(18)(19)(20)(21)59). Unfortunately, aside from standard information presented in species description papers, little information is available regarding the physiological capabilities, adaptive mechanisms, and genomic characteristics of these genera.…”
Section: Figmentioning
confidence: 64%
See 2 more Smart Citations
“…Prior studies have identified members of the Halorubrum and Haloquadratum and, in some samples, Halonotius, Natrinema, and Haloferax as dominant members of crystallizer salterns (8,45,47), while in our study, members of the recently described genera Halogranum, Halolamina, Halosarcina Halorientalis, and Haloplanus represented a major fraction of the Halobacteriales community in multiple habitats (e.g., 60.8, 66.4, 41.1, and 49.4% in MAN, ZDT, CAR, and SPL, respectively). This attests to the relevance and significance of recent efforts for the isolation and characterization of novel Halobacteriales genera in various habitats beyond typical hypersaline water bodies (14)(15)(16)(17)(18)(19)(20)(21)59). Unfortunately, aside from standard information presented in species description papers, little information is available regarding the physiological capabilities, adaptive mechanisms, and genomic characteristics of these genera.…”
Section: Figmentioning
confidence: 64%
“…do not appear to be well adapted to low-salinity habitats such as Zodletone Spring ( Table 2). The genus Halolamina contains only one described species, which has recently been isolated from an artificial marine saltern in China (17). Halolamina-associated sequences were most abundant in sediments from the Great Salt Plains, mangrove, and Zodletone Spring, suggesting their adaptability to survive in environments with various degrees of salinity fluctuations (Table 2).…”
Section: Diversity Patterns In Halobacteriales Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutral oligotrophic haloarchaeal medium (NOM-3) containing 100 mg streptomycin ml 21 and 100 mg ampicillin ml 21 was used in the initial enrichment (Cui et al, 2011). The soil samples were collected from a salt mine located in Baicheng County, Xinjiang province, China.…”
mentioning
confidence: 99%
“…Twenty-two transformants of strain BC12-B1 T were G V picked randomly and sequenced to determine whether the strain possessed multiple distinct 16S rRNA genes. Multiple sequence alignments were performed as described by Cui et al (2011). The sequence was aligned with closely related 16S rRNA gene sequences by the EzTaxon-e server (Kim et al, 2012) and BLAST (http://blast.ncbi.nlm.nih.gov/ Blast.cgi).…”
mentioning
confidence: 99%